FBM students win awards at the International Project Logistics Competition at Raffles University - Bahrudin, Nur Zahidah (UiTM, 2023)
Students from FBM achieved awards at the International Project Logistics Competition held at Raffles University. The competition provided a platform for students to demonstrate project management and logistics skills while fostering teamwork and international collaboration.